Karst und Terra rossa auf Mallorca - Mensching, Horst (ERDKUNDE, 1955)
In September 1954, the author investigated the Mediterranean karst, the terra rossa and the quaternary gravel sheets in the coastal mountains of Majorca, the largest of the Balearic Islands. He concluded that the Mediterranean terra rossa must be viewed in genetical and chronological connexion with the quaternary gravel sheets. The karst features also belong mainly to the series of landforms which owe their origin to quaternary conditions. In the coastal mountains of Majorca the slopes above 500 m. are frequently covered by thick gravel sheets in conjunction with terra rossa; these have also filled the extensive karst depressions and poljes. These red-earth gravel sheets must have originated in the last quaternary (Würm) period. It is assumed that the quaternary glacial periods, which on the isle were just eff :ective as pluvial periods, offered particularly favourable conditions for the formation of the Mediterranean terra rossa. By largely fluviatile transport this quaternary terra rossa was brought into the central plain of Majorca, which today is covered by a soil of striking red colour. Besides the extensive karst depressions and quaternary karst caves on the coast of the Sierra de Levante (Arta and Porto Cristo) there are also found post-quaternary sharp-edged karren of pyramidal shape which occur in impressive karren fields in the coastal mountains especially at an altitude of 800-1,000 m. During the Pleistocene glacial periods, the Isle of Majorca occupied a transitional position between the cold zones of Middle Europe and North Africa where pluvial conditions prevailed